Організація єврейської світської освіти у Києві у 1918–1922 рр. - Уманська, А. (Краєзнавство, 2020)
У статті висвітлено тему організації єврейської світської освіти у Києві у 20-х рр. ХХ ст., що здійснювалася за ініціативи культурно-просвітницької організації «Культур-Ліга». Проаналізовано історичний контекст та передумови постання організації, концепцію нової світської їдишської культури для Східноєвропейського єврейства, запропоновану Культур-Лігою, та шляхи її втілення. На прикладі освітніх закладів, ініційованих організацією, висвітлено шляхи впровадження новітньої їдишської освітньої моделі. Розглянуто низку їдишських навчальних закладів Культур-Ліги, зокрема дитячі садки, гімназії, школи для дорослих, Єврейський Народний Університет та мережу бібліотек. The Outline of the Problem. Backgrounds of the formation and spreading of the Jewish public educational institutions started in the nineteenth century. Majority of the educational institutions were established by the Jewish civic and cultural-educational organization «Kultur-Lige». Specifically, the Jewish public Yiddish schools, public libraries and reading rooms, as well as Jewish Public University were functioned under the direction of Kultur-Lige. Methods of Research. The main methods, used in the article, are the method of synthetic analysis and quantitative method. The method of retrospection was also used by the author. Survey of the Results. The article is about the organization of the Jewish public education in Kyiv in 1918- 1922 functioned under the initiative of the cultural-educational organization «Kultur-Lige». Historical background and conditions of formation of the organization, conception of new public Yiddish culture for East European Jewry and ways of its realization were analyzed by the author. The example of educational institutions organized by Kultur-Lige showed the ways of incorporation of new Yiddish educational model. The Yiddish educational institutions such as kindergartens, gymnasiums, courses for adults, Jewish Public University and library network are examined in the article. Conclusions. Despite the unstable political environment in Kyiv in 1917-1922, there was collaboration between members of the Jewish communities and cultural-educational organizations, especially Kultur-Lige, with the local Ukrainian government. Educational institutions organized by Kultur-Lige provided education for all categories of the Jewish community. The author analyzed that educational network included few preschool institutions, secondary schools, gymnasiums, evening classes for adults, teachers' training college and Jewish Public University. All these institutions were secular with Yiddish as a language of teaching.